Identity construction and impression management across digital sport platforms: a PRISMA 2020 systematic review of studies published between 2015 and 2026 - Anisa Sholiha Mia; Bram Sujadesman; Jeki Haryanto (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
With the rise of social media, there is a change in the way athletes create, manage and convey their images. They no longer depend on traditional media outlets to shape their reputation but can now use digital platforms to craft their image directly. While there have been lots of studies in this field that span sport sociology, sport communication, and digital media, most results are disjointed, and there is barely any research on how self-presentation, impression management, athletic identity and personal branding come together in the connected context. This review attempts to fill some gaps in the literature by consolidating the empirical works done on athletes' self-presentation in digital environments. According to the PRISMA 2020 guidelines, a Scopus search was carried out that turned up 649 documents. The Scopus search was conducted in January 2026 using the search terms